Priorities in Global Assistance for Health, Aids and Population (HAP) - MacKellar, Landis (OECD Development Centre Working Papers, 2005)
In this paper, trends in official development assistance (ODA) for Health AIDS and Population (HAP) are analysed to gain information about revealed priorities. The major findings are as follows: HIV/AIDS is clearly the top priority in international health assistance. While the share of HAP in total ODA has increased significantly over the last decade, however, if HIV/AIDS is excluded, health assistance is actually losing, not gaining share in total ODA. Even more striking, apart from HIV/AIDS, the health sub-sectors generally considered pro-poor are losing share in health ODA. These trends, inconsistent with the emphasis placed on health as a key sector in development and with growing recognition of the links between health and poverty, are true both for aid-recipient countries as a whole and for least-developed countries. They help to explain and underscore the urgency of warnings emanating from the international public health community that international support for health development is insufficient. They also raise the issue of whether HAP assistance is being effectively allocated to address the needs of the poor....